Missionary Writings during the Canton Exile (1666–1671): Crisis in the Manchu-Christian Relationship - Thierry Meynard (Religions, 2024)
During their Canton exile (1666–1671), European missionaries wrote an impressive number of reports and letters which have not been systematically studied until now. After presenting a detailed analysis of the institutional background of the 25 missionaries who arrived in Canton, we analyze the first internal reports about the Calendar Case. Then, we discuss three important Jesuit works by Gabiani, Grelon and Rougemont, who attributed the crisis to the opposition of the Manchus to Christianity. The distrust of the Canton Jesuits towards the Manchus throws a new light into the approach of Christianity towards politics and religion in China.